Expression Profile of Genes Related to the Th17 Pathway in Macrophages Infected by Leishmania major and Leishmania amazonensis: The Use of Gene Regulatory Networks in Modeling This Pathway - Gonçalves, Leilane Oliveira; Pulido, Andrés F. Vallejo; Mathias, Fernando Augusto Siqueira; Enes, Alexandre Estevão Silvério; Carvalho, Maria Gabriela Reis; de Melo Resende, Daniela; Polak, Marta E.; Ruiz, Jeronimo C. (Frontiers in Cellular and Infection Microbiology, 2022)
Leishmania amazonensis and L. major are the causative agents of cutaneous and mucocutaneous diseases. The infection's outcome depends on host-parasite interactions and Th1/Th2 response and, in cutaneous form, regulation of Th17 cytokines has been reported to maintain inflammation in lesions. Despite that, the Th17 regulatory scenario remains unclear. Aiming a better understanding of the transcriptional factors (TF) and genes involved in Th17 induction, in this work, the role of Th17 pathway in Leishmania-macrophage infection was addressed through a computational modeling of gene regulatory networks (GRNs). The Th17 GRN modeling integrated experimentally validated data, available in literature, and gene expression data from a time-series RNAseq experiment (4, 24, 48 and 72 hours post-infection). The generated model comprises a total of 10 TF, 22 coding genes and 16 cytokines related to the Th17 immune modulation. Addressing the Th17 induction in infected and uninfected macrophages, it was observed in the first one an increase of 2-3 fold in the 4-24h. However, there was a decrease to basal levels at 48-72h for both groups. In order to evaluate the possible outcomes triggered by GRNs components modulation in the Th17 pathway, a simulation was performed resulting in 30% of inhibition of the full pathway. The generated GRN models promoted an integrative and dynamic view of Leishmania-macrophage interaction over time that goes beyond the analysis of single gene expression.